1992
DOI: 10.1017/s0954102092000270
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activities of Antarctic sponges

Abstract: Methanol-toluene extracts of 17 common Antarctic marine sponges collected from shallow waters in McMurdo Sound in October-December 1989 were tested for suppression of growth of bacteria (gram-positive and negative), yeasts and fungi. Weak to moderate levels of antimicrobial activity occurred in all sponges. Antimicrobial activity was more common when gram-negative bacteria were exposed to sponge extracts; 47% of the sponge extracts caused growthinhibition inone or more gram-positive bacteria, while 100% of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 15 publications
3
17
0
Order By: Relevance
“…Our data are generally in line with those obtained by McClintock and Gauthier [20], who screened non-polar extracts of 17 Antarctic sponges for inhibitory activities against bacteria and fungi. They showed particularly strong inhibitory activities associated with extracts from the sponge species belonging to the genera Latrunculia and Haliclona .…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Our data are generally in line with those obtained by McClintock and Gauthier [20], who screened non-polar extracts of 17 Antarctic sponges for inhibitory activities against bacteria and fungi. They showed particularly strong inhibitory activities associated with extracts from the sponge species belonging to the genera Latrunculia and Haliclona .…”
Section: Resultssupporting
confidence: 91%
“…Sponges are known to contain a high number of compounds that act against terrestrial pathogenic bacteria, while considerably lower activities have been observed against marine bacteria [18]. Furthermore, in comparison with sponges found in temperate and tropical seas, Antarctic sponges have been reported to have a smaller number of antimicrobial secondary metabolites [19] that show generally weaker activities [20]. Previous screenings of crude extracts from 93 Arctic sponges against bacteria and fungi associated with opportunistic infections showed that about 10% of the sponges yielded significant antimicrobial activities, with IC 50 values from 0.2 to 5 μg/mL [5].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…P. invaginata collected from Antarctica, has been shown to inhibit both Gram-negative and Gram-positive bacteria (McClintock and Gauthier, 1992). A steroid/amino acid conjugate, Polymastiamide A, isolated from the Norwegian sponge, P. boletiformis, was found to be active against various human pathogens including S. aureus and C. albicans (Kong and Anderssen, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Antimicrobial Assays In addition to predator deterrence, many secondary metabolites have antimicrobial activities, and in sponges, this is probably the major source of pathogen immunity (McClintock and Gauthier, 1992;Newbold et al, 1999). Disk diffusion assays were used to test the presence of antibacterial activity in the organic extracts of healthy and ARBS-affected sponges, and pure compounds of A. cauliformis, against a panel of 8 bacteria.…”
Section: Isolation and Quantification Of Pure Compoundsmentioning
confidence: 99%